Vocabulary learning in virtual environments: Learner autonomy and collaboration. (February 2020) - Tseng, Wen-Ta; Liou, Hao-Jyuan; Chu, Hsi-Chin
Abstract: Three-dimensional (3D) virtual environments provide EFL learners with a rich and dynamic multimodal context for vocabulary learning. This study aims to investigate the effects of implementing a 3D vocabulary learning program on EFL young learners' vocabulary acquisition. Specifically, the interplay between two learning factors – learner autonomy and collaboration – were investigated to examine the effects of the social-cultural dimension of such practice. A quasi-experimental research design was undertaken to examine the effects of 3D virtual environment mediation, learner autonomy, and pair-work cooperation on vocabulary learning. The findings supported the positive effect of virtual environments in facilitating vocabulary learning. In addition, individual use and paired autonomous use, which dovetail with the design nature of the program, instigated a more profound retention of vocabulary than teacher-directed use. Importantly, pair-work was found to enhance longer retention than individual practice. It is suggested that successful vocabulary learning on a 3D program lies not only in the autonomous control of the learners per se but also in their active engagement with the artifacts as well as their close collaboration with partners.